Atuação do Núcleo de Apoio Contábil e Fiscal (NAF) da UPF Passo Fundo para os contribuintes atendidos na realização da Declaração de imposto de Renda Pessoa Física - Camargo, Eliseu Spagnol (2024)
The University of Passo Fundo is one of the institutions that supports and develops in partnership with the Federal Revenue of Brazil, the Accounting and Fiscal Support Center - NAF, a project that aims to provide future accounting professionals with the opportunity to better qualify through practice based on helping people with lower contributory capacity. Thus, this research aimed to carry out a study on the role of NAF in University of Passo Fundo to complete the income tax declaration (IRPF) at year 2024. The methodology adopted to meet the general objective consisted of a diagnostic research, characterized as descriptive in terms of objectives, method mixed, with a technical field research procedure with 78 contributors, who sought service for the project between April and May 2024. It is concluded, at the end of the work, that the profile of taxpayers served is represented by people from the city of Passo Fundo, male (54%), contributory age group over 50 years old (54%), have high school education (38%), have an income (82%), compared to an accountant's salary 60% responded that they would pay between R$75 and R$150. In relation to the NAF, taxpayers report that they already made the declaration last year (60%); that the work was satisfactory or that is, it solved the problem (88%) and 100% would recommend the project to friends.